2016
DOI: 10.3390/su8030226
|View full text |Cite
|
Sign up to set email alerts
|

The Local Residents’ Concerns about Environmental Issues in Northwest China

Abstract: This paper analyzes public awareness and perception about current issues of environmental and water resources in China in comparison to the socio-economic issues. The ranking, Likert scale, and ordered logit analysis were applied to data from 1773 sample residents in northwest China. The results show that the residents rank the degradation of the ecological environment and water resources as the most important issue, and education, political involvement, gender, employment, and residential location play signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…The results also indicated that poverty reduction and infrastructure had mean values of 5.22 and 4.74, respectively and they were considered the least important issues. Due to considerable reductions in poverty [62,85] and the construction of infrastructure [86,87] in the last 45 years, poverty is no longer an issue in Northwest China but this achievement has been obtained at the cost of environmental degradation [64,65] and health risks [88].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results also indicated that poverty reduction and infrastructure had mean values of 5.22 and 4.74, respectively and they were considered the least important issues. Due to considerable reductions in poverty [62,85] and the construction of infrastructure [86,87] in the last 45 years, poverty is no longer an issue in Northwest China but this achievement has been obtained at the cost of environmental degradation [64,65] and health risks [88].…”
Section: Resultsmentioning
confidence: 99%
“…The largest and highly sandy tributary of the Yellow River called the Wei River is located in the arid and semiarid region of Northwest China [61], as shown in Figure 1, where it flows through three geographical areas comprising the Loess plateau—Guangzhong basin in Shaanxi province and the North Qinling Mountains [62]. The Guangzhong area is located in the middle and lower reaches of the Wei River and it covers almost 135,000 km 2 (about 50%) of the entire river basin [55,63].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental problems occur in many countries, such as India (Bhattacharyya et al, 2015), China (Aregay, Zhao, Li, Xia, & Chen, 2016), Vietnam (Nguyen, Lin, & Chan, 2019), and Indonesia. One city that has environmental problems in Indonesia is Bandung (Septian, Ruhimat, & Somantri, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Like in many developing countries, water resources (e.g., quality, quantity, etc.) are the most severe and challenging issues in the Chinese public's eyes (e.g., [43]). Thus, this research explored this challenging issue through questioning a new engineering generation who will be involved in water-related projects in China in the future.…”
Section: Discussionmentioning
confidence: 99%